Urban crime prevention and the logics of public security policies in Brazil – a relational perspective on the local fields of negotiation - Haubrich, Dominik; Wehrhahn, Rainer (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
Public security is a highly contested issue in urban societies. It involves, stresses or excludes a wide spectrum of actors, policies and spaces on different scales and time lapse. Meanwhile, public security possesses a central position in the recent transcontextual discussion of area-based urban security studies. Therein, both questions of social change and the spatial, political and economical reflection of (in)security issues are increasingly concerning the current transforming logic of public security policies. To capture this transformation from a theoretical as well as empirical perspective, this papers looks at the local security governance field in the municipality of São Paulo. It argues that the political field of local crime prevention councils (CONSEG), hosted on the district level once a month, is suited to understand the conceptual shift of the crime control paradigm in general and its spatial translation into discourses, programs, instruments and measures of local security provision in particular.